A case study in institutional repository content curation: A collaborative partner approach to preserving and sustaining digital scholarship. Issue 1 (13th February 2017) - Miller, A.
Abstract : Purpose: The purpose of this case study is to illustrate how a university library collaborated with a specific college to preserve scholarship with a sustainable approach. The practical process described is recommended for increasing content submissions in a newly established institutional repository. Of the eight colleges at Middle Tennessee State University (MTSU), the Honors College was selected as a case study for a library–college collaboration on content curation for the institutional repository that is maintained by MTSU's Walker Library. Design/methodology/approach: Concept of shared and divided responsibilities for the upload, maintenance and sustainability of institutional repository submissions based on a particular case study and aided with literature on data management, digital publishing, library publishing and preservation research. Findings: The partner approach, the sharing and division of responsibilities, is instrumental to the growth and sustainability of a library publishing program and for the preservation of university scholarship. Practical implications: The (college) partner approach not only educates campus units about a new resource (e.g. institutional repository), but also encourages campus units to rethink other current and outdated practices that need to adapt to technological changes that support the unit and its students. This approach will help the library with campus outreach after an institutional repository is implemented and offers guidance on a collaborative approach to repository submission growth. Originality/value: This paper suggests a (college) partner approach that mutually benefits the College and its students, departments and the library that maintains the institutional repository on behalf of the university. During the implementation process of this case study, an Americans with Disabilities Act (ADA)/accessibility compliance issue of repository items surfaced and allowed for a new course of action to be taken campus wide which adds to the originality of this case study.